An empirical analysis of the effects of student work and academic performance on the probability of employment - Bartolj, Tjaša (Economic and business review, 2021)
The theoretical relationship between student work and post-college probability of employment is ambiguous, due to the opposing direct and indirect effects on human capital accumulation. Student work may on one hand lower academic performance and thus harm the likelihood of getting a job, while on the other hand enabling students to acquire skills that increase their labour market odds. In this paper, we provide an answer to the question, whether the policy should encourage or limit student work, by using rich data which allow us to compare the effects of the two investments in human capital on the likelihood of employment. We use personal characteristics, socio-economic background, and academic performance in the propensity score matching to calculate the differences in the probability of employment for different amounts of student work. We find that only work experiences up to two years have a beneficial effect on employment prospects, while much larger effects are observed for improvements in educational attainment, like graduation and improvement in GPA. In the end, our results provide support for setting limits to the extent of student work during college, but certainly not for its prohibition.
Keywords: education; employment; izobrazba; labour market; student work; študentsko delo; trg dela; zaposlovanje